This looks like you can do the same thing as last time. can you write down the equation we have to solve?
yes, I know that. but both right hand sides equal y so they equal each other. can you write that down?
no, i still not gettin it because its a lot to remember
y=-5x-6 y=-8x-6 if -5x-6 equals y, you can replace y in the 2nd equation with -5x-6. Can you write that down?
go it written down
what do you have?
am i doing y=-5x-6
you have 2 equations y=-5x-6 y=-8x-6 the 1st equation says y is -5x-6 that means you can replace y in the 2nd equation with -5x-6. after you do that what is this new equation?
what happened to the other side and what happened to the = ? If we had y= A and y= SOMETHING we can replace y with A in the 2nd equation: A= SOMETHING can you use that same idea with y=-5x-6 y=-8x-6
sorry so it would be -8x-6=-5x-6
yes. now that you have an equation, you can find x I would start by adding +6 to both sides -8x -6+6 = -5x-6+6 can you simplify this?
I would simplify -6+6 to 0
okay, i go that then whats next
what do you have so far?
yes and you can simplify -5x+0 , right? what do you get?
I get -8x= -5x if you add +8x to both sides you get 8x-8x = 8x-5x of course 8x - 8x is 0 (you have 8x and take away 8x, to get 0) 0= 8x-5x on the right side, you have 8x and take away 5x, what do you have left?
@jackyluvv would you mind helping me with one more
@jackyluvv please read the Code of Conduct
sorry @phi if i did anything wrong